Dietary effects of cottonseed and vitamin E on greenhouse gas emissions from cattle feces analyzed in biodigesters - Ricardo Galbiatti Sandoval Nogueira; Flavio Perna Junior; Ramos Jorge Tseu; Paulo Henrique Mazza Rodrigues (Pesquisa Agropecuária Brasileira, 2023)
Abstract The objective of this work was to evaluate the effect of diets with cottonseed and vitamin E on the greenhouse gas (GHG) emissions of cattle feces analyzed in biodigesters. Animal feces were evaluated in 18 laboratory-scale anaerobic digesters through the following treatments: control, feces from cows fed with a control diet; CS, feces from cows fed with a cottonseed diet; and CSVitE, feces from cows fed with a cottonseed and vitamin E diet. The production of biogas and GHG was measured, and no differences were observed for the emissions of biogas, methane (CH4), and nitrous oxide (N2O). The partition of the gross energy of the anaerobic digestion process was similar among treatments. On average, 28% of gross energy fed was released as CH4, 47% during digestion, and 25% as other gases and heat. The addition of cottonseeds to the cattle diet increases the concentration of CH4 and reduces that of CO2, but it does not affect the total production of CH4, CO2, and N2O in the biodigesters. The inclusion of vitamin E in the diet has no effect on GHG production in the biodigesters.